Pengaruh Suhu Permukaan Laut terhadap Hasil Tangkapan Ikan Cakalang (Katsuwonus pelamis) di Perairan Selat Bali - I Gusti Agung Gede Bayu Gita Damara; I Gusti Bagus Sila Dharma; Yulianto Suteja (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
This study aims to examine the effect of sea surface temperature on the skipjack tuna catch (Katsuwonus pelamis) in the waters of the Bali Strait. The waters of the Bali strait are selected by the authors because the waters of the Bali strait have the potential of catching tuna fish is high. The research is measured by using regression polynomial method of order 2. With the results of this study found from the sea surface temperature data in the results of the average - the average year 2011 - 2015 where the highest value is in March at 30.240C and the lowest in September of 25.870C. For skipjack catch data in 2011 - 2015 where the lowest weight in June was 4. 590 kg, while the highest weight in July was 61,367 kg, and beside that the result of regression 2nd polynomial regression was obtained with R = - 0.60 which has a strong meaning is inversely proportional or in other words sea surface temperature does not affect the catching of skipjack tuna in the waters of bali strait because in addition to sea surface temperature factors other indicators such as chlorophyll, depth, and oceanographic factors also affect the catch skipjack tuna in the waters of the bali strait.